Dance Team Double Trouble - Jake Maddox (Stone Arch Books, 2021)
When twins Lydia and Marco are approached to be on their dance studio's jazz team, Lydia is thrilled. She and Marco both love to dance and used to have fun dancing together as kids. But lately it seems their relationship has grown more distant. Lydia can't wait to dance with her brother again, but Marco is worried. He's used to hip-hop and will be the only boy on the team. And when bullies start mocking Marco for doing girl dances it could spell trouble for the whole team.
Keywords: Sports Stories -- Sports Stories